Journal of Engineering, Science and Technology at the Crossroads of Science and Education: A Bibliometric Review (2009–2025) - Abdulkareem Sh. Mahdi Al-Obaidi (Bumi Publikasi Nusantara, 2025)
This study presents a bibliometric analysis of publications in the Journal of Engineering, Science and Technology (JESTEC) indexed in Scopus from 2009 to July 2025, consisting of 3,825 documents. The analysis explores publication trends, geographic distribution, citation metrics, keyword frequency, and thematic clusters. Findings reveal a steady growth in international authority and highlight the increasing prominence of education-related research, particularly in topics aligned with the Sustainable Development Goals (SDGs), such as energy systems, waste valorization, and digital tools. Notably, 964 documents (over 25% of total publications) were identified as education-focused, with a peak in 2023. This trend underscores JESTEC's evolving role as not only a scientific journal but also a platform for educational innovation. The study suggests that JESTEC could further enhance its impact by formally recognizing education-driven research within its editorial direction, reflecting the real-world application of science and engineering through instructional design and training.